PENGGUNAAN MEDIA ROLLINGBALL ISLAMI MATERI SIFAT WAJIB DAN MUSTAHIL BAGI RASUL DI MAJLIS TA’LIM ALHIKMAH KARAWANG - Azzahra, Amalia; Abdurrohim, Abdurrohim; Mustofa, Taufik; pengelola, pengelola (LPPM STAI Ihyaul Ulum Gresik, 2025)
The problem discussed in this study is about how the use of Islamic rollingball media is mandatory for apostles, this research was conducted at the Majlis Ta'lim Al-Hikmah Karawang, this research used a qualitative descriptive method, this study resulted in that the use of this Islamic rollingball game media easy to use and makes the spirit of learning. The world of education in Indonesia is increasingly experiencing significant developments. This point of development can be seen from the increasing variety of learning methods used. The methods used make use of various media to improve the quality of learning outcomes. One of them uses an Islamic rolling ball. The purpose of this research is to increase students' interest in studying the obligatory and impossible nature of the apostle and to reduce students' fear and low self-confidence. This research uses a qualitative approach. This approach tends to use inductive analysis, in which research and the giving of meaning to data and information are highlighted through the main characteristic, namely the descriptive form. The data sources used in this study were students, teachers and parents. Lots of problems that arise when learning to use this Rolling ball media. Starting from lessons that are less interesting, difficult, and lazy to learn, so that this affects the enthusiasm for learning PAI and makes students ignore lessons and do not understand these lessons at home.